Analisis Kehujjahan Maqāṣid al-Syarī‘ah sebagai Dasar Ijtihad dalam Menyelesaikan Persoalan Hukum Islam Kontemporer - Rudi Hartono; M. Sahrir; Jamaluddin Jamaluddin (Lembaga Yasin AlSys, 2026)
Although maqāṣid al-sharīʿah has received significant attention in various studies of Islamic law, research that specifically examines the authoritative status of maqāṣid al-sharīʿah as a methodological foundation for ijtihād in addressing contemporary issues of Islamic law remains relatively limited and tends to be normative-descriptive. This study aims to analyze the status of the authoritative force (ḥujjiyyah) of maqāṣid al-sharīʿah from the perspective of uṣūl fiqh and to explain its relevance for the development of Islamic legal ijtihād amid modern social dynamics. The study employs a qualitative approach with a library research design through a normative-philosophical lens. Data were obtained from critical analyses of the works of classical and contemporary scholars, including al-Shāṭibī, Ibn Qayyim al-Jawziyyah, al-Shawkānī, Abdullahi Ahmed An-Na‘im, and other relevant literature, and were then analyzed thematically and comparatively to examine arguments for the authoritative status of maqāṣid and its application in ijtihād practice. The findings show that maqāṣid al-sharīʿah possesses strong legitimacy as a basis for ijtihād, since all Islamic legal rulings are essentially oriented toward the realization of maṣlaḥah (benefit) and the prevention of harm. This maṣlaḥah is realized through the preservation of the five essential interests (al-kulliyyāt al-khams), namely religion, life, intellect, lineage, and property, which are classified into the levels of ḍarūriyyāt, ḥājiyyāt, and taḥsīniyyāt. The study also affirms that maqāṣid-based ijtihād has been practiced since the time of the Prophet Muhammad and his Companions, particularly in the legal policies of ʿUmar ibn al-Khaṭṭāb, who took changing social contexts into account. The conclusion emphasizes that a sound understanding of maqāṣid al-sharīʿah is a key factor in maintaining the flexibility, dynamism, and relevance of Islamic law in responding to contemporary challenges. The implications of this research include a theoretical contribution to enriching the corpus of uṣūl fiqh and contemporary ijtihād, as well as practical implications for mujtahids, academics, and Islamic legal policymakers in formulating legal solutions that are oriented toward maṣlaḥah and the development of a civil society. This study also opens avenues for further research on developing more applicable models of maqāṣidī ijtihād within modern social contexts.